Impact of Methamphetamine Abuse: A Rare Case of Rapid Cerebral Aneurysm Growth with Review of Literature. (4th October 2018) - Fowler, James; Fiani, Brian; Quadri, Syed A.; Cortez, Vladimir; Frooqui, Mudassir; Zafar, Atif; Ahmed, Fahad Shabbir; Ikram, Asad; Ramachandran, Anirudh; Siddiqi, Javed
Abstract : Methamphetamine or "meth" is a sympathomimetic amine of the amphetamine-type substances (ATS) class with an extremely high potential for abuse. Illicitly abused neurostimulants like cocaine and meth predispose patients to the aneurysmal formation with reported rupture at a younger age and in much smaller sized aneurysms. However, very rapid growth of aneurysm within less than 2 weeks with methamphetamine abuse is very rarely observed or reported. In this report, we present a patient with repeated and recurrent meth abuse who demonstrated rapid growth of a pericallosal aneurysm over the period of less than two weeks. The pathophysiology of stroke related to meth and ATS abuse is multifactorial with hypertension, tachycardia, and vascular disease postulated as major mechanisms. The rapid growth of an aneurysm has a high risk of aneurysmal rupture and SAH, which is a neurosurgical emergency and therefore warrants careful consideration and close monitoring. This case confirms the dynamic temporal effects of methamphetamine use on intracranial vessels and this specific neurostimulants association to rapid aneurysmal formation. In light of vascular pathologies the possibility of drug-induced pseudoaneurysm should also be considered in young patients with history of meth abuse.